Antihypertensive activity of roasted cashew nut in mixed petroleum fractions-induced hypertension: An in vivo and in silico approaches - Jacob Kehinde Akintunde; Victoria Omoyemi Akomolafe; Odunayo Anthonia Taiwo; Iqrar Ahmad; Harun Patel; Adeola Osifeso; Adefuye Oluwafemi Olusegun; Oluwafemi Adeleke Ojo (Heliyon, 2022)
Consumption of water polluted by crude oil is a major environmental problem typical in exploration areas. Numerous health complications such as high blood pressure, myocardial infarction, and other heart complications are prevalent and ravaging. These have gradually become age-defiling disease conditions that are usually maintained with lifestyle changes and diet control. The effect of dietary supplementation with 10% and 20% roasted cashew nuts (RCN) on systolic blood pressure and angiotensin converting enzyme I (ACE I) activities in mixed petroleum fraction (MPF) induced toxicity was studied in male Wistar rats through the modulation of the renin-angiotensin system. The phytochemicals in RCN were quantified using the high performance liquid chromatography (HPLC) technique. To predict likely binding affinity and stability, computational methods such as molecular docking, ADME, and molecular dynamic simulation were used. Out of the seven phytochemicals identified, rutin, gallic acid, and quercetin had the greatest quantities. Similarly, rutin had the highest binding affinities with ACE I, -10.7 kcal/mol, followed by quercetin, at -9.1 kcal/mol. During the molecular dynamics simulation, all of the identified phytochemicals demonstrated good pharmacokinetic capabilities and remained stable at their respective binding sites. Subsequent in vivo validation studies revealed that RCN was able to attenuate the effect of MPF by significantly (p < 0.05) lowering the systolic blood pressure and ACE I activity in comparison to the reference medication, atenolol. We recommend that cashew nuts be explored as dietary snacks as well as a low-cost, easily available component of supplements for the treatment of high blood pressure.